Trivalent recombinant protein vaccine induces cross-neutralization against XBB lineage and JN.1 subvariants: preclinical and phase 1 clinical trials - Jingyun Yang; Weiqi Hong; Huashan Shi; Cai He; Hong Lei; Yanan Zhou; Hao Yang; Aqu Alu; Zimin Chen; Yun Yang; Wenhai Yu; Cong Tang; et al. (Nature Communications)
Abstract The immune escape capacities of XBB variants necessitate the authorization of vaccines with these antigens. In this study, we produce three recombinant trimeric proteins from the RBD sequences of Delta, BA.5, and XBB.1.5, formulating a trivalent vaccine (Tri-Vac) with an MF59-like adjuvant at a 1:1:4 ratio. Tri-Vac demonstrates immunogenicity in female NIH mice, inducing cross-neutralization against various SARS-CoV-2 variants, including pre-Omicron and Omicron BA.2.75, BA.5, and XBB lineages. It elicits measurable antigen-specific T cell responses, germinal center B cell responses, and T follicular helper responses, effectively protecting against live Omicron XBB.1.16 challenges. Protective immunity is maintained long-term, with sustained neutralizing antibodies and T cell responses, as well as memory B cells and long-lived plasma cells observed by day 210 post-immunization. Tri-Vac also serves as a candidate booster for enhancing immunity after three doses of inactivated virus or mRNA vaccines. A phase 1 investigator-initiated trial was initiated to assess safety and immunogenicity in humans, focusing on the primary endpoint of adverse reactions within 7 days and key secondary endpoints including the geometric mean titers (GMTs) of serum neutralizing antibodies within 30 days and 6 months post-vaccination, as well as adverse events within 30 days and serious adverse events within 6 months post-vaccination. Preliminary data indicate Tri-Vac has good safety and immunogenicity, improving neutralization against multiple variants, including JN.1, in previously vaccinated individuals, highlighting its clinical potential for protecting against SARS-CoV-2 variants. The registration number of this clinical trial is ChiCTR2200067245.